1997
DOI: 10.1097/00005768-199704000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of treadmill running on lipoprotein(a) levels in males and females

Abstract: This investigation examined the acute response of serum lipoprotein(a) (Lp(a)) concentration immediately after, and during several days following, level and downhill motorized treadmill running. Eight males ran for 1 h on a level motorized treadmill at an intensity producing 90% maximum heart rate (MHR). On a separate occasion, three males and three females performed downhill (negative 13.4% incline) treadmill running at an intensity producing 75-80% MHR. For both protocols, serial blood samples were taken pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Moreover, as endothelial cells release t-PA and PAI-1, it has also been suggested that they could be related as marker of endothelial cell damage or dysfunction [19]. Finally, Lp(a) levels were decreased at plasma 30 minutes after exercise, possibly related to an improvement of fibrinolytic capacity, in contrast to studies that have failed to find a relationship between exercise and changes in plasma Lp(a) levels [20][21][22][23]. Smoking habit did not modify our findings, in spite of the basal high levels of Lp(a) observed in smokers compared to non smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as endothelial cells release t-PA and PAI-1, it has also been suggested that they could be related as marker of endothelial cell damage or dysfunction [19]. Finally, Lp(a) levels were decreased at plasma 30 minutes after exercise, possibly related to an improvement of fibrinolytic capacity, in contrast to studies that have failed to find a relationship between exercise and changes in plasma Lp(a) levels [20][21][22][23]. Smoking habit did not modify our findings, in spite of the basal high levels of Lp(a) observed in smokers compared to non smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Similar effects were reported on muscle tissue and in blood samples from groups of healthy individuals, suggesting that repeated muscle biopsies by itself may explain some of the previously reported signs of muscle inflammation; it is still uncertain how much muscle inflammation is caused by exercise itself [47•]. Furthermore, an acute raise of s-CK levels after physical exercise has been reported in numerous studies of healthy individuals [48•] usually returning to normal about 3 days post exercise [49]. During the past decade, 10 published studies have evaluated the safety and benefits of resistive exercise in patients with IIM, seven in polymyositis or dermatomyositis, and two in inclusion body myositis, and one study including all three ( Table 2).…”
Section: Exercise In Patients With Idiopathic Inflammatory Myopathiesmentioning
confidence: 99%
“…Sixty minutes of level and 40 min of downhill treadmill running did not evoke significant changes in CRP. 36 Similarly, elevated CRP was not seen as an acute consequence of typical training of elite female netball and soccer teams. 37 Twenty-four maximal eccentric arm curls did not evoke significant alterations in CRP levels in 14 untrained males.…”
Section: Discussionmentioning
confidence: 95%